Method for preparing single-walled carbon nanotube through arc discharge

By introducing a non-catalytically active component A into the arc discharge method as a nucleation site and surface property regulator, the problems of catalyst instability and low single-walled carbon nanotube content were solved, and the efficient growth and improvement of single-walled carbon nanotubes were achieved.

CN120922856APending Publication Date: 2025-11-11PEKING UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410559758.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-08
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

In existing technologies, the preparation of single-walled carbon nanotubes by arc discharge method suffers from problems such as catalyst instability, loss of activity, and low content of single-walled carbon nanotubes in the resulting samples.

Method used

Component A, which has no catalytic activity, is introduced as a nucleation site and surface property regulator in the gas-phase nucleation process of metal catalysts. This includes oxides of silicon and oxides of phosphorus, etc., to regulate the formation of metal catalysts, prevent their deactivation, and promote the growth of single-walled carbon nanotubes.

Benefits of technology

This effectively maintains the stability of the catalyst and improves the content and quality of single-walled carbon nanotubes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120922856A_ABST
    Figure CN120922856A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing a single-walled carbon nanotube through arc discharge, and belongs to the technical field of carbon nanotube preparation, the method comprises the following steps: preparing an anode comprising a metal catalyst, a carbon raw material and a component A without catalytic activity, and placing the anode and a pure graphite rod cathode in an electric arc furnace; and introducing a set atmosphere into the electric arc furnace, enabling the cathode to be in contact with the anode and enabling a set current to pass through, increasing the distance between the cathode and the anode after conduction so as to maintain arc discharge, continuously consuming the anode under the action of the arc, and collecting the generated gray black carbon nanotube product on the furnace wall. According to the method provided by the invention, the component A without catalytic activity is introduced as a nucleation site, a dispersed phase and a surface property regulating agent in the gas phase nucleation process of the metal catalyst, so that the formation of the metal catalyst can be effectively regulated, the stability of the metal catalyst is maintained, the inactivation of the metal catalyst is avoided, the growth of the single-walled carbon nanotube can be promoted, and the service life of the single-walled carbon nanotube is prolonged. And the content of the single-walled carbon nanotubes in the obtained sample is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of carbon nanotube preparation technology, and in particular to a method for preparing single-walled carbon nanotubes by arc discharge. Background Technology

[0002] Single-walled carbon nanotubes (SWCNTs) have shown promising applications in various electronic devices such as thin-film transistors, conductive electrodes, and sensors due to their extremely high electron and hole mobility and suitable and tunable band gap.

[0003] There are three main methods for synthesizing single-walled carbon nanotubes (SWCNTs): arc discharge, laser, and chemical vapor deposition. Among them, SWCNTs prepared by arc discharge have a higher degree of graphitization and fewer defects, resulting in superior electrical and thermal properties. Currently, most raw materials for carbon-based nanoelectronic devices are prepared by arc discharge. The synthesis of carbon nanotubes in the arc follows a gas-phase growth path. Under the combined action of current heating and electron bombardment, carbon in the anode sublimates or sputters out in the form of atoms or clusters, and then gradually condenses and nucleates along the temperature gradient to form carbon nanotubes.

[0004] In existing technologies, the preparation of single-walled carbon nanotubes by arc discharge method suffers from problems such as catalyst instability, loss of activity, and low content of single-walled carbon nanotubes in the obtained samples during the gas phase growth of carbon nanotubes. Summary of the Invention

[0005] The present invention aims to provide a method for preparing single-walled carbon nanotubes by arc discharge, so as to overcome the shortcomings of the prior art. The technical problem to be solved by the present invention is achieved through the following technical solution.

[0006] The method for preparing single-walled carbon nanotubes by arc discharge provided by the present invention includes:

[0007] An anode comprising a metal catalyst, a carbon raw material, and a non-catalytically active component A is prepared. The anode and a pure graphite rod cathode are placed in an electric arc furnace. The non-catalytically active component A comprises elemental silicon, elemental phosphorus, elemental arsenic, elemental selenium, elemental tellurium, elemental iodine, oxides of silicon, oxides of phosphorus, oxides of arsenic, oxides of selenium, oxides of tellurium, oxides of iodine, oxides of titanium, oxides of vanadium, oxides of manganese, oxides of copper, oxides of zinc, oxides of germanium, oxides of niobium, oxides of molybdenum, oxides of silver, oxides of tin, oxides of antimony, oxides of lanthanum, oxides of tantalum, oxides of tungsten, oxides of lead, oxides of bismuth, hydroxides of titanium, hydroxides of vanadium, hydroxides of manganese, hydroxides of copper, and hydroxides of zinc. One or more of the following: germanium hydroxide, niobium hydroxide, molybdenum hydroxide, silver hydroxide, tin hydroxide, antimony hydroxide, lanthanum hydroxide, tantalum hydroxide, tungsten hydroxide, lead hydroxide, bismuth hydroxide, salts containing silicon, salts containing phosphorus, salts containing arsenic, salts containing selenium, salts containing tellurium, salts containing iodine, salts containing vanadium, salts containing manganese, salts containing copper, salts containing zinc, salts containing germanium, salts containing niobium, salts containing molybdenum, salts containing silver, salts containing tin, salts containing antimony, salts containing lanthanum, salts containing tantalum, salts containing tungsten, salts containing lead, and salts containing bismuth;

[0008] A set atmosphere is introduced into the electric arc furnace, the cathode and anode are brought into contact and a set current is passed through. After conduction, the distance between the cathode and anode is increased to maintain the electric arc discharge. Under the action of the electric arc, the anode is continuously consumed, and the generated gray-black carbon nanotube products are collected on the furnace wall.

[0009] In the above scheme, the non-catalytically active component A is one or more of the following: silicon oxide, phosphorus oxide, titanium oxide, manganese oxide, copper oxide, zinc oxide, molybdenum oxide, tungsten oxide, titanium hydroxide, manganese hydroxide, copper hydroxide, zinc hydroxide, molybdenum hydroxide, tungsten hydroxide, salts containing silicon, salts containing phosphorus, salts containing titanium, salts containing manganese, salts containing copper, salts containing zinc, salts containing molybdenum, and salts containing tungsten.

[0010] In the above scheme, the non-catalytically active component A is made of elemental silicon, silicon dioxide, potassium phosphate, titanium hydroxide, manganese monoxide, copper chloride, zinc chloride, sodium molybdate, lanthanum sulfate, tantalum oxide, tungsten trioxide, or lead monoxide.

[0011] In the above scheme, the metal catalyst is one or more of the following: scandium, chromium, iron, cobalt, nickel, yttrium, zirconium, ruthenium, rhodium, palladium, cerium, rhenium, osmium, iridium, scandium oxide, chromium oxide, iron oxide, cobalt oxide, nickel oxide, yttrium oxide, zirconium oxide, ruthenium oxide, rhodium oxide, palladium oxide, cerium oxide, rhenium oxide, osmium oxide, iridium oxide, scandium sulfide, chromium sulfide, iron sulfide, cobalt sulfide, nickel sulfide, yttrium sulfide, zirconium sulfide, ruthenium sulfide, rhodium sulfide, palladium sulfide, cerium sulfide, rhenium sulfide, osmium sulfide, and iridium sulfide.

[0012] In the above scheme, the metal catalyst is selected from two or three of the following: elemental iron, elemental cobalt, elemental nickel, elemental yttrium, iron oxide, cobalt oxide, nickel oxide, yttrium oxide, iron sulfide, cobalt sulfide, nickel sulfide, and yttrium sulfide.

[0013] In the above scheme, the amount of component A without catalytic activity is 0-100 times that of the metal catalyst, and the amount of component A without catalytic activity is 0-5 times that of the carbon raw material.

[0014] In the above scheme, the atmosphere introduced into the electric arc furnace is one or two of hydrogen, helium, nitrogen, and argon.

[0015] In the above scheme, the total pressure in the electric arc furnace is 30kPa-100kPa before the cathode and anode are brought into contact.

[0016] In the above scheme, the distance between the cathode and the anode is 1mm-20mm during the arc discharge process.

[0017] In the above scheme, the arc discharge current is 40-80A and the arc discharge voltage is 15-50V.

[0018] The embodiments of the present invention have the following advantages:

[0019] The method for preparing single-walled carbon nanotubes by arc discharge provided in this invention introduces a component A that has no catalytic activity as a nucleation site, dispersed phase and surface property regulator in the gas-phase nucleation process of the metal catalyst. This can effectively regulate the formation of the metal catalyst, maintain its stability and avoid its deactivation, thereby promoting the growth of single-walled carbon nanotubes and increasing the content of single-walled carbon nanotubes in the obtained sample. Attached Figure Description

[0020] Figure 1 This is a step diagram of a method for preparing single-walled carbon nanotubes by electric arc discharge according to the present invention;

[0021] Figure 2 This is a scanning electron microscope image of the carbon nanotubes prepared in the first embodiment of the present invention;

[0022] Figure 3 This is a scanning electron microscope image of the carbon nanotubes prepared in the fourth embodiment of the present invention;

[0023] Figure 4 This is a scanning electron microscope image of the carbon nanotubes prepared in the eighth embodiment of the present invention;

[0024] Figure 5 This is a scanning electron microscope image of the carbon nanotubes prepared in the ninth embodiment of the present invention;

[0025] Figure 6 This is a scanning electron microscope image of the carbon nanotubes prepared in the comparative example of the present invention.

[0026] Figure 7 These are the Raman spectra of the carbon nanotubes prepared in the first embodiment and the comparative example of the present invention at a wavelength of 532 nm.

[0027] Figure 8 These are the Raman spectra of the carbon nanotubes prepared in the second embodiment and the comparative example of the present invention at a wavelength of 532 nm.

[0028] Figure 9 These are the Raman spectra of the carbon nanotubes prepared in the third embodiment and the comparative example of the present invention at a wavelength of 532 nm.

[0029] Figure 10 These are the Raman spectra of the carbon nanotubes prepared in the fourth embodiment and the comparative example of the present invention at a wavelength of 532 nm.

[0030] Figure 11 These are the Raman spectra of the carbon nanotubes prepared in the fifth embodiment and comparative example of the present invention at a wavelength of 532 nm.

[0031] Figure 12 These are the Raman spectra of the carbon nanotubes prepared in the sixth embodiment and the comparative example of the present invention at a wavelength of 532 nm.

[0032] Figure 13 These are the Raman spectra of the carbon nanotubes prepared in the seventh embodiment and the comparative example of the present invention at a wavelength of 532 nm.

[0033] Figure 14 These are the Raman spectra of the carbon nanotubes prepared in the eighth embodiment and the comparative example of the present invention at a wavelength of 532 nm.

[0034] Figure 15These are the Raman spectra of carbon nanotubes prepared in the ninth embodiment and comparative example of the present invention at a wavelength of 532 nm.

[0035] Figure 16 These are the Raman spectra of carbon nanotubes prepared in the tenth embodiment and comparative example of the present invention at a wavelength of 532 nm.

[0036] Figure 17 These are the Raman spectra of the carbon nanotubes prepared in the eleventh embodiment and the comparative example of the present invention at a wavelength of 532 nm.

[0037] Figure 18 These are the Raman spectra of the carbon nanotubes prepared in the twelfth embodiment and the comparative example of the present invention at a wavelength of 532 nm.

[0038] Figure 19 These are the absorption spectra of the carbon nanotubes prepared in the first embodiment and the comparative example of the present invention.

[0039] Figure 20 These are the absorption spectra of the carbon nanotubes prepared in the second embodiment and the comparative example of the present invention.

[0040] Figure 21 These are the absorption spectra of the carbon nanotubes prepared in the third embodiment and the comparative embodiment of the present invention.

[0041] Figure 22 These are the absorption spectra of the carbon nanotubes prepared in the fourth embodiment and the comparative example of the present invention.

[0042] Figure 23 These are the absorption spectra of the carbon nanotubes prepared in the fifth embodiment and the comparative example of the present invention.

[0043] Figure 24 These are the absorption spectra of the carbon nanotubes prepared in the sixth embodiment and the comparative example of the present invention.

[0044] Figure 25 These are the absorption spectra of the carbon nanotubes prepared in the seventh embodiment and the comparative example of the present invention.

[0045] Figure 26 These are the absorption spectra of the carbon nanotubes prepared in the eighth embodiment and the comparative example of the present invention.

[0046] Figure 27 These are the absorption spectra of the carbon nanotubes prepared in the ninth embodiment and the comparative example of the present invention.

[0047] Figure 28 These are the absorption spectra of the carbon nanotubes prepared in the tenth embodiment and comparative example of the present invention.

[0048] Figure 29These are the absorption spectra of the carbon nanotubes prepared in the eleventh embodiment and the comparative example of the present invention.

[0049] Figure 30 These are the absorption spectra of the carbon nanotubes prepared in the twelfth embodiment and the comparative example of the present invention.

[0050] Figure 31 The thermogravimetric curve and its first derivative plot of the carbon nanotubes prepared according to the sixth embodiment of the present invention are shown.

[0051] Figure 32 The thermogravimetric curve and its first derivative plot of the carbon nanotubes obtained in the eighth embodiment of the present invention are shown.

[0052] Figure 33 The thermogravimetric curves and their first derivative plots of the carbon nanotubes prepared according to the comparative example of this invention are shown. Detailed Implementation

[0053] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the accompanying drawings and embodiments.

[0054] like Figure 1 As shown, this invention provides a method for preparing single-walled carbon nanotubes by arc discharge, the method comprising the following steps:

[0055] Step S1: Prepare an anode comprising a metal catalyst, carbon raw material and component A which has no catalytic activity, and place the anode and a pure graphite rod cathode in an electric arc furnace;

[0056] Specifically, the metal catalyst is selected from elemental scandium, elemental chromium, elemental iron, elemental cobalt, elemental nickel, elemental yttrium, elemental zirconium, elemental ruthenium, elemental rhodium, elemental palladium, elemental cerium, elemental rhenium, elemental osmium, elemental iridium, oxides of scandium, oxides of chromium, oxides of iron, oxides of cobalt, oxides of nickel, oxides of yttrium, oxides of zirconium, oxides of ruthenium, oxides of rhodium, oxides of palladium, oxides of cerium, oxides of rhenium, oxides of osmium, oxides of iridium, sulfides of scandium, sulfides of chromium, sulfides of iron, sulfides of cobalt, sulfides of nickel, sulfides of yttrium, sulfides of zirconium, sulfides of ruthenium, and sulfides of rhodium. The sample contains one or more of the following: scandium, palladium sulfide, cerium sulfide, rhenium sulfide, osmium sulfide, and iridium sulfide; preferably, scandium oxide, iron oxide, cobalt oxide, nickel oxide, yttrium oxide, scandium sulfide, iron sulfide, cobalt sulfide, nickel sulfide, and yttrium sulfide; more preferably, two or three of the following: iron oxide, cobalt oxide, nickel oxide, yttrium oxide, iron oxide, cobalt oxide, nickel oxide, yttrium oxide, iron sulfide, cobalt sulfide, nickel sulfide, and yttrium sulfide.

[0057] Specifically, the carbon raw material can be selected from one or more of graphite, coal, carbon black, coke, activated carbon, amorphous carbon, and biomass carbon, preferably one or two of graphite, coal, and carbon black, and more preferably graphite.

[0058] Specifically, the non-catalytically active component A can be selected from one or more of the following: elemental silicon, elemental phosphorus, elemental arsenic, elemental selenium, elemental tellurium, elemental iodine, oxides of silicon, oxides of phosphorus, oxides of arsenic, oxides of selenium, oxides of tellurium, oxides of iodine, salts containing silicon, salts containing phosphorus, salts containing arsenic, salts containing selenium, salts containing tellurium, and salts containing iodine.

[0059] Specifically, component A, which lacks catalytic activity, can also be selected from oxides of titanium, vanadium, manganese, copper, zinc, germanium, niobium, molybdenum, silver, tin, antimony, lanthanum, tantalum, tungsten, lead, bismuth, titanium hydroxide, vanadium hydroxide, manganese hydroxide, copper hydroxide, zinc hydroxide, germanium hydroxide, niobium hydroxide, molybdenum hydroxide, silver hydroxide, and tin hydroxide. One or more of the following: oxides, antimony hydroxides, lanthanum hydroxides, tantalum hydroxides, tungsten hydroxides, lead hydroxides, bismuth hydroxides, oxides containing titanium, salts containing vanadium, salts containing manganese, salts containing copper, salts containing zinc, salts containing germanium, salts containing niobium, salts containing molybdenum, salts containing silver, salts containing tin, salts containing antimony, salts containing lanthanum, salts containing tantalum, salts containing tungsten, salts containing lead, and salts containing bismuth.

[0060] Specifically, the non-catalytically active component A is preferably one or more of the following: silicon oxide, phosphorus oxide, titanium oxide, manganese oxide, copper oxide, zinc oxide, molybdenum oxide, tungsten oxide, titanium hydroxide, manganese hydroxide, copper hydroxide, zinc hydroxide, molybdenum hydroxide, tungsten hydroxide, salts containing silicon, salts containing phosphorus, salts containing titanium, salts containing manganese, salts containing copper, salts containing zinc, salts containing molybdenum, and salts containing tungsten; more preferably, it is one or more of the following: titanium oxide, manganese oxide, copper oxide, zinc oxide, molybdenum oxide, tungsten oxide, titanium hydroxide, manganese hydroxide, copper hydroxide, zinc hydroxide, molybdenum hydroxide, tungsten hydroxide, salts containing titanium, salts containing manganese, salts containing copper, salts containing zinc, salts containing molybdenum, and salts containing tungsten.

[0061] Specifically, the amount of component A, which has no catalytic activity, is 0-1000 times that of the metal catalyst, preferably 0.1-100 times, and more preferably 1-10 times.

[0062] Specifically, the amount of component A, which has no catalytic activity, is 0-100 times that of the carbon raw material, preferably 0-5 times, and more preferably 0-0.5 times.

[0063] Specifically, by introducing a component A that has no catalytic activity as a nucleation site, dispersed phase and surface property regulator in the gas-phase nucleation process of metal catalysts, the formation of metal catalysts can be effectively regulated, their stability maintained and their deactivation avoided, thereby promoting the growth of single-walled carbon nanotubes and increasing the content of single-walled carbon nanotubes in the obtained samples.

[0064] Step S2: Introduce the set atmosphere into the electric arc furnace, bring the cathode and anode into contact and allow the set current to pass through. After conduction, increase the distance between the cathode and anode to maintain the electric arc discharge. Under the action of the electric arc, the anode is continuously consumed, and the generated gray-black carbon nanotube products are collected on the furnace wall.

[0065] Specifically, the atmosphere introduced into the electric arc furnace is one or more of hydrogen, helium, nitrogen, argon, methane, carbon monoxide, air, water, methanol, and ethanol, preferably one or more of hydrogen, helium, nitrogen, argon, carbon monoxide, and air, and more preferably one or two of hydrogen, helium, nitrogen, and argon.

[0066] Specifically, before the cathode and anode come into contact, the total pressure in the electric arc furnace is 2 kPa-1000 kPa, preferably 10 kPa-200 kPa, and more preferably 30 kPa-100 kPa;

[0067] Specifically, the circuit is made to be connected by bringing the cathode and anode into contact, and then the cathode and anode are pulled apart to generate a discharge arc;

[0068] Specifically, the current of the arc discharge is 30-150A, preferably 35-110A, and more preferably 40-80A;

[0069] Specifically, the voltage of the electric arc discharge is 15-50V;

[0070] Specifically, during the arc discharge process, the distance between the cathode and the anode is set to be 1mm-20mm;

[0071] Specifically, during the arc discharge process, the area near the arc core contains component A, which has no catalytic activity, or its reaction products;

[0072] Specifically, under the action of the electric arc, the anode is continuously consumed, while the non-catalytically active component A, the metal catalyst, and carbon are evaporated.

[0073] In the first embodiment of the present invention, a density of 1.85 g·cm³ is used. -3 A perforated graphite rod with an outer diameter of 6 mm, an inner diameter of 4 mm, a hole depth of 40 mm, and a total length of 60 mm was made from graphite. A mixed powder with a weight ratio of graphite:nickel:cobalt:iron:silicon dioxide = 5:6:6:1:30 was prepared and filled into the perforated graphite rod to prepare the anode. At this time, in the consumable part of the anode, the amount of silicon dioxide used was 0.104 times the amount of graphite used, and the amount of silicon dioxide used was 2.32 times the total amount of nickel, cobalt, and iron used. A pure graphite rod with a diameter of 8 mm was used as the cathode. The two electrodes were placed horizontally opposite each other. The electric arc furnace cavity was evacuated to below 20 Pa, and helium gas was introduced at 30 kPa. This was repeated three times. The cathode and anode were brought into contact. The DC welding arc power supply was turned on, the distance between the cathode and anode was adjusted to 8 mm, the discharge current was adjusted to 60 A, and the arc discharge lasted for about 5 minutes. The generated gray-black carbon nanotube products were collected on the furnace wall.

[0074] The carbon nanotubes prepared in the first embodiment were tested using a scanning electron microscope, and the images are as follows. Figure 2 As shown, by Figure 2 It can be seen that the content of single-walled carbon nanotubes is higher after the introduction of silica, indicating that the introduction of silica has a promoting effect on the growth of single-walled carbon nanotubes.

[0075] In the second embodiment of the present invention, a density of 1.85 g·cm³ is used. -3 A perforated graphite rod with an outer diameter of 6 mm, an inner diameter of 4 mm, a hole depth of 40 mm, and a total length of 60 mm was made from graphite. A mixed powder with a weight ratio of graphite:nickel:cobalt:iron:silicon = 5:6:6:1:30 was prepared and filled into the perforated graphite rod to prepare the anode. At this time, the amount of silicon in the consumable part of the anode was 0.191 times the amount of graphite, and the amount of silicon was 4.96 times the total amount of nickel, cobalt, and iron. A pure graphite rod with a diameter of 8 mm was used as the cathode. The two electrodes were placed horizontally opposite each other. The electric arc furnace cavity was evacuated to below 20 Pa, and helium gas was introduced at 30 kPa. This process was repeated three times. The cathode and anode were brought into contact. The DC welding arc power supply was turned on, the distance between the cathode and anode was adjusted to 8 mm, the discharge current was adjusted to 60 A, and the arc discharge lasted for about 5 minutes. The generated gray-black carbon nanotube products were collected on the furnace wall.

[0076] In the third embodiment of the present invention, a density of 1.85 g·cm³ is used. -3A perforated graphite rod with an outer diameter of 6 mm, an inner diameter of 4 mm, a hole depth of 40 mm, and a total length of 60 mm was made from graphite. A mixed powder with a weight ratio of graphite:nickel:cobalt:iron:potassium phosphate = 5:6:6:1:30 was prepared and filled into the perforated graphite rod to prepare the anode. At this time, the amount of potassium phosphate in the consumable part of the anode was 0.025 times the amount of graphite, and the amount of potassium phosphate was 0.66 times the total amount of nickel, cobalt, and iron. A pure graphite rod with a diameter of 8 mm was used as the cathode. The two electrodes were placed horizontally opposite each other. The electric arc furnace cavity was evacuated to below 20 Pa, and helium gas was introduced at 30 kPa. This process was repeated three times. The cathode and anode were brought into contact. The DC welding arc power supply was turned on, the distance between the cathode and anode was adjusted to 8 mm, the discharge current was adjusted to 60 A, and the arc discharge lasted for about 5 minutes. The generated gray-black carbon nanotube products were collected on the furnace wall.

[0077] In the fourth embodiment of the present invention, a density of 1.85 g·cm³ is used. -3 A perforated graphite rod with an outer diameter of 6 mm, an inner diameter of 4 mm, a hole depth of 40 mm, and a total length of 60 mm was made from graphite. A mixed powder with a weight ratio of graphite:nickel:cobalt:iron:titanium hydroxide = 5:6:6:1:30 was prepared and filled into the perforated graphite rod to prepare the anode. At this time, the amount of titanium hydroxide in the consumable part of the anode was 0.045 times the amount of graphite, and the amount of titanium hydroxide was 1.20 times the total amount of nickel, cobalt, and iron. A pure graphite rod with a diameter of 8 mm was used as the cathode. The two electrodes were placed horizontally opposite each other. The electric arc furnace cavity was evacuated to below 20 Pa, and helium gas was introduced at 30 kPa. This process was repeated three times. The cathode and anode were brought into contact. The DC welding arc power supply was turned on, the distance between the cathode and anode was adjusted to 8 mm, the discharge current was adjusted to 60 A, and the arc discharge lasted for about 5 minutes. The generated gray-black carbon nanotube products were collected on the furnace wall.

[0078] The carbon nanotubes prepared in the fourth embodiment were tested using a scanning electron microscope, and the images are as follows. Figure 3 As shown, by Figure 3 It can be seen that the content of single-walled carbon nanotubes is higher after the introduction of titanium hydroxide, indicating that the introduction of titanium hydroxide has a promoting effect on the growth of single-walled carbon nanotubes.

[0079] In the fifth embodiment of the present invention, a density of 1.85 g·cm³ is used. -3A perforated graphite rod with an outer diameter of 6 mm, an inner diameter of 4 mm, a hole depth of 40 mm, and a total length of 60 mm was made from graphite. A mixed powder with a weight ratio of graphite:nickel:cobalt:iron:manganese monoxide = 5:6:6:1:30 was prepared and filled into the perforated graphite rod to prepare the anode. At this time, the amount of manganese monoxide in the consumable part of the anode was 0.089 times the amount of graphite, and the amount of manganese monoxide was 1.96 times the total amount of nickel, cobalt, and iron. A pure graphite rod with a diameter of 8 mm was used as the cathode. The two electrodes were placed horizontally opposite each other. The electric arc furnace cavity was evacuated to below 20 Pa, and helium gas was introduced at 30 kPa. This process was repeated three times. The cathode and anode were brought into contact. The DC welding arc power supply was turned on, the distance between the cathode and anode was adjusted to 8 mm, the discharge current was adjusted to 60 A, and the arc discharge lasted for about 5 minutes. The generated gray-black carbon nanotube products were collected on the furnace wall.

[0080] In the sixth embodiment of the present invention, a density of 1.85 g·cm³ is used. -3 A perforated graphite rod with an outer diameter of 6 mm, an inner diameter of 4 mm, a hole depth of 40 mm, and a total length of 60 mm was made from graphite. A mixed powder with a weight ratio of graphite:nickel:cobalt:iron:copper chloride = 5:6:6:1:30 was prepared and filled into the perforated graphite rod to prepare the anode. At this time, the amount of copper chloride in the consumable part of the anode was 0.045 times the amount of graphite, and the amount of copper chloride was 1.04 times the total amount of nickel, cobalt, and iron. A pure graphite rod with a diameter of 8 mm was used as the cathode. The two electrodes were placed horizontally opposite each other. The electric arc furnace cavity was evacuated to below 20 Pa, and helium gas was introduced at 30 kPa. This process was repeated three times. The cathode and anode were brought into contact. The DC welding arc power supply was turned on, the distance between the cathode and anode was adjusted to 8 mm, the discharge current was adjusted to 60 A, and the arc discharge lasted for about 5 minutes. The generated gray-black carbon nanotube products were collected on the furnace wall.

[0081] In the seventh embodiment of the present invention, a density of 1.85 g·cm³ is used. -3 A perforated graphite rod with an outer diameter of 6 mm, an inner diameter of 4 mm, a hole depth of 40 mm, and a total length of 60 mm was made from graphite. A mixed powder with a weight ratio of graphite:nickel:cobalt:iron:zinc chloride = 5:6:6:1:30 was prepared and filled into the perforated graphite rod to prepare the anode. At this time, the amount of zinc chloride in the consumable part of the anode was 0.063 times the amount of graphite, and the amount of zinc chloride was 1.02 times the total amount of nickel, cobalt, and iron. A pure graphite rod with a diameter of 8 mm was used as the cathode. The two electrodes were placed horizontally opposite each other. The electric arc furnace cavity was evacuated to below 20 Pa, and helium gas was introduced at 30 kPa. This process was repeated three times. The cathode and anode were brought into contact. The DC welding arc power supply was turned on, the distance between the cathode and anode was adjusted to 8 mm, the discharge current was adjusted to 60 A, and the arc discharge lasted for about 5 minutes. The generated gray-black carbon nanotube products were collected on the furnace wall.

[0082] In the eighth embodiment of the present invention, a density of 1.85 g·cm³ is used. -3 A perforated graphite rod with an outer diameter of 6 mm, an inner diameter of 4 mm, a hole depth of 40 mm, and a total length of 60 mm was made from graphite. A mixed powder with a weight ratio of graphite:nickel:cobalt:iron:sodium molybdate = 5:6:6:1:30 was prepared and filled into the perforated graphite rod to prepare the anode. At this time, the amount of sodium molybdate in the consumable part of the anode was 0.031 times the amount of graphite, and the amount of sodium molybdate was 0.68 times the total amount of nickel, cobalt, and iron. A pure graphite rod with a diameter of 8 mm was used as the cathode. The two electrodes were placed horizontally opposite each other. The electric arc furnace cavity was evacuated to below 20 Pa, and helium gas was introduced at 30 kPa. This was repeated three times. The cathode and anode were brought into contact. The DC welding arc power supply was turned on, the distance between the cathode and anode was adjusted to 8 mm, the discharge current was adjusted to 60 A, and the arc discharge lasted for about 5 minutes. The generated gray-black carbon nanotube products were collected on the furnace wall.

[0083] The carbon nanotubes prepared in the eighth embodiment were tested using a scanning electron microscope, and the images are as follows. Figure 4 As shown, by Figure 4 It can be seen that the content of single-walled carbon nanotubes is higher after the introduction of sodium molybdate, indicating that the introduction of sodium molybdate has a promoting effect on the growth of single-walled carbon nanotubes.

[0084] In the ninth embodiment of the present invention, a density of 1.85 g·cm³ is used. -3 A perforated graphite rod with an outer diameter of 6 mm, an inner diameter of 4 mm, a hole depth of 40 mm, and a total length of 60 mm was made from graphite. A mixed powder with a weight ratio of graphite:nickel:cobalt:iron:lanthanum sulfate = 5:6:6:1:30 was prepared and filled into the perforated graphite rod to prepare the anode. At this time, the amount of lanthanum sulfate in the consumable part of the anode was 0.023 times the amount of graphite, and the amount of lanthanum sulfate was 0.49 times the total amount of nickel, cobalt, and iron. A pure graphite rod with a diameter of 8 mm was used as the cathode. The two electrodes were placed horizontally opposite each other. The electric arc furnace cavity was evacuated to below 20 Pa, and helium gas was introduced at 30 kPa. This was repeated three times. The cathode and anode were brought into contact. The DC welding arc power supply was turned on, the distance between the cathode and anode was adjusted to 8 mm, the discharge current was adjusted to 60 A, and the arc discharge lasted for about 5 minutes. The generated gray-black carbon nanotube products were collected on the furnace wall.

[0085] The carbon nanotubes prepared in the ninth embodiment were tested using a scanning electron microscope, and the images are as follows. Figure 5 As shown, by Figure 5 It can be seen that the content of single-walled carbon nanotubes is higher after the introduction of lanthanum sulfate, indicating that the introduction of lanthanum sulfate has a promoting effect on the growth of single-walled carbon nanotubes.

[0086] In the tenth embodiment of the present invention, a density of 1.85 g·cm³ is used. -3A perforated graphite rod with an outer diameter of 6 mm, an inner diameter of 4 mm, a hole depth of 40 mm, and a total length of 60 mm was made from graphite. A mixed powder with a weight ratio of graphite:nickel:cobalt:iron:tantalum oxide = 5:6:6:1:30 was prepared and filled into the perforated graphite rod to prepare the anode. At this time, the amount of tantalum oxide in the consumable part of the anode was 0.032 times the amount of graphite, and the amount of tantalum oxide was 0.63 times the total amount of nickel, cobalt, and iron. A pure graphite rod with a diameter of 8 mm was used as the cathode. The two electrodes were placed horizontally opposite each other. The electric arc furnace cavity was evacuated to below 20 Pa, and helium gas was introduced at 30 kPa. This process was repeated three times. The cathode and anode were brought into contact. The DC welding arc power supply was turned on, the distance between the cathode and anode was adjusted to 8 mm, the discharge current was adjusted to 60 A, and the arc discharge lasted for about 5 minutes. The generated gray-black carbon nanotube products were collected on the furnace wall.

[0087] In the eleventh embodiment of the present invention, a density of 1.85 g·cm³ is used. -3 A perforated graphite rod with an outer diameter of 6 mm, an inner diameter of 4 mm, a hole depth of 40 mm, and a total length of 60 mm was made from graphite. A mixed powder with a weight ratio of graphite:nickel:cobalt:iron:tungsten trioxide = 5:6:6:1:30 was prepared and filled into the perforated graphite rod to prepare the anode. At this time, the amount of tungsten trioxide in the consumable part of the anode was 0.032 times the amount of graphite, and the amount of tungsten trioxide was 0.60 times the total amount of nickel, cobalt, and iron. A pure graphite rod with a diameter of 8 mm was used as the cathode. The two electrodes were placed horizontally opposite each other. The electric arc furnace cavity was evacuated to below 20 Pa, and helium gas was introduced at 30 kPa. This process was repeated three times. The cathode and anode were brought into contact. The DC welding arc power supply was turned on, the distance between the cathode and anode was adjusted to 8 mm, the discharge current was adjusted to 60 A, and the arc discharge lasted for about 5 minutes. The generated gray-black carbon nanotube products were collected on the furnace wall.

[0088] In the twelfth embodiment of the present invention, a density of 1.85 g·cm³ is used. -3 A perforated graphite rod with an outer diameter of 6 mm, an inner diameter of 4 mm, a hole depth of 40 mm, and a total length of 60 mm was made from graphite. A mixed powder with a weight ratio of graphite:nickel:cobalt:iron:lead monoxide = 5:6:6:1:30 was prepared and filled into the perforated graphite rod to prepare the anode. At this time, the amount of lead monoxide in the consumable part of the anode was 0.035 times the amount of graphite, and the amount of lead monoxide was 0.62 times the total amount of nickel, cobalt, and iron. A pure graphite rod with a diameter of 8 mm was used as the cathode. The two electrodes were placed horizontally opposite each other. The electric arc furnace cavity was evacuated to below 20 Pa, and helium gas was introduced at 30 kPa. This process was repeated three times. The cathode and anode were brought into contact. The DC welding arc power supply was turned on, the distance between the cathode and anode was adjusted to 8 mm, the discharge current was adjusted to 60 A, and the arc discharge lasted for about 5 minutes. The generated gray-black carbon nanotube products were collected on the furnace wall.

[0089] In the comparative example of this invention, a density of 1.85 g·cm³ was used. -3 A perforated graphite rod with an outer diameter of 6 mm, an inner diameter of 4 mm, a hole depth of 40 mm, and a total length of 60 mm was made from graphite. A mixed powder with a weight ratio of graphite:nickel:cobalt:iron = 5:6:6:1 was prepared and filled into the perforated graphite rod to prepare the anode. A pure graphite rod with a diameter of 8 mm was used as the cathode. The two electrodes were placed horizontally opposite each other. The electric arc furnace cavity was evacuated to below 20 Pa, and helium gas was introduced at 30 kPa. This process was repeated three times. The cathode and anode were brought into contact. The DC welding arc power supply was turned on. The distance between the cathode and anode was adjusted to 8 mm, and the discharge current was adjusted to 60 A. The arc discharge lasted for about 5 minutes. The gray-black carbon nanotube products generated were collected on the furnace wall.

[0090] The carbon nanotubes prepared in the comparative example were tested using a scanning electron microscope. The images are as follows: Figure 6 As shown, by Figure 6 It can be seen that the content of single-walled carbon nanotubes is low when no non-catalytically active component A is added, indicating that the introduction of non-catalytically active component A has a promoting effect on the growth of single-walled carbon nanotubes.

[0091] Specifically, Raman spectroscopy was used to perform Raman tests on the carbon nanotubes prepared in the first embodiment, second embodiment, third embodiment, fourth embodiment, fifth embodiment, sixth embodiment, seventh embodiment, eighth embodiment, ninth embodiment, tenth embodiment, eleventh embodiment, twelfth embodiment and comparative example at a laser wavelength of 532 nm.

[0092] The Raman spectra of the carbon nanotubes prepared in the first embodiment and the comparative embodiment at a wavelength of 532 nm are shown below. Figure 7 As shown, the Raman spectral intensity of the carbon nanotube sample prepared in the first embodiment under 532 nm excitation is higher than that of the corresponding Raman spectral intensity in the comparative example, indicating that the introduction of silica has a promoting effect on the growth of carbon nanotubes.

[0093] The Raman spectra of the carbon nanotubes prepared in the second embodiment and the comparative embodiment at a wavelength of 532 nm are shown below. Figure 8 As shown, the Raman spectral intensity of the carbon nanotube sample prepared in the second embodiment under 532 nm excitation is higher than that of the corresponding Raman spectral intensity in the comparative example, indicating that the introduction of silicon has a promoting effect on the growth of carbon nanotubes.

[0094] The Raman spectra of the carbon nanotubes prepared in the third embodiment and the comparative embodiment at a wavelength of 532 nm are shown below. Figure 9 As shown, the Raman spectral intensity of the carbon nanotube sample prepared in the third embodiment under 532 nm excitation is higher than that of the corresponding Raman spectral intensity in the comparative example, indicating that the introduction of potassium phosphate has a promoting effect on the growth of carbon nanotubes.

[0095] The Raman spectra of the carbon nanotubes prepared in the fourth embodiment and the comparative embodiment at a wavelength of 532 nm are shown below. Figure 10 As shown, the Raman spectral intensity of the carbon nanotube sample prepared in the fourth embodiment under 532 nm excitation is higher than that of the corresponding Raman spectral intensity in the comparative example, indicating that the introduction of titanium hydroxide has a promoting effect on the growth of carbon nanotubes.

[0096] The Raman spectra of the carbon nanotubes prepared in the fifth embodiment and the comparative example at a wavelength of 532 nm are shown below. Figure 11 As shown, the Raman spectral intensity of the carbon nanotube sample prepared in the fifth embodiment under 532 nm excitation is higher than that of the corresponding Raman spectral intensity in the comparative example, indicating that the introduction of manganese monoxide has a promoting effect on the growth of carbon nanotubes.

[0097] The Raman spectra of the carbon nanotubes prepared in the sixth embodiment and the comparative example at a wavelength of 532 nm are shown below. Figure 12 As shown, the Raman spectral intensity of the carbon nanotube sample prepared in the sixth embodiment under 532 nm excitation is higher than that of the corresponding Raman spectral intensity in the comparative example, indicating that the introduction of copper chloride has a promoting effect on the growth of carbon nanotubes.

[0098] The Raman spectra of the carbon nanotubes prepared in the seventh embodiment and the comparative embodiment at a wavelength of 532 nm are shown below. Figure 13 As shown, the Raman spectral intensity of the carbon nanotube sample prepared in the seventh embodiment under 532 nm excitation is higher than that of the corresponding Raman spectral intensity in the comparative example, indicating that the introduction of zinc chloride has a promoting effect on the growth of carbon nanotubes.

[0099] The Raman spectra of the carbon nanotubes prepared in the eighth embodiment and the comparative embodiment at a wavelength of 532 nm are shown below. Figure 14 As shown, the Raman spectral intensity of the carbon nanotube sample prepared in the eighth embodiment under 532 nm excitation is higher than that of the corresponding Raman spectral intensity in the comparative example, indicating that the introduction of sodium molybdate has a promoting effect on the growth of carbon nanotubes.

[0100] The Raman spectra of the carbon nanotubes prepared in the ninth embodiment and the comparative embodiment at a wavelength of 532 nm are shown below. Figure 15 As shown, the Raman spectral intensity of the carbon nanotube sample prepared in the ninth embodiment under 532 nm excitation is higher than that of the corresponding Raman spectral intensity in the comparative example, indicating that the introduction of lanthanum sulfate has a promoting effect on the growth of carbon nanotubes.

[0101] The Raman spectra of the carbon nanotubes prepared in the tenth embodiment and the comparative example at a wavelength of 532 nm are shown below. Figure 16As shown, the Raman spectral intensity of the carbon nanotube sample prepared in the tenth embodiment under 532 nm excitation is higher than that of the corresponding Raman spectral intensity in the comparative example, indicating that the introduction of tantalum oxide has a promoting effect on the growth of carbon nanotubes.

[0102] The Raman spectra of the carbon nanotubes prepared in the eleventh embodiment and the comparative example at a wavelength of 532 nm are shown below. Figure 17 As shown, the Raman spectral intensity of the carbon nanotube sample prepared in the eleventh embodiment under 532 nm excitation is higher than that of the corresponding Raman spectral intensity in the comparative example, indicating that the introduction of tungsten trioxide has a promoting effect on the growth of carbon nanotubes.

[0103] The Raman spectra of the carbon nanotubes prepared in the twelfth embodiment and the comparative example at a wavelength of 532 nm are shown below. Figure 18 As shown, the Raman spectral intensity of the carbon nanotube sample prepared in the twelfth embodiment under 532 nm excitation is higher than that of the corresponding Raman spectral intensity in the comparative example, indicating that the introduction of lead monoxide has a promoting effect on the growth of carbon nanotubes.

[0104] Specifically, 1 mg of the carbon nanotube sample prepared in the first embodiment, 1 mg of the carbon nanotube sample prepared in the second embodiment, 1 mg of the carbon nanotube sample prepared in the third embodiment, 1 mg of the carbon nanotube sample prepared in the fourth embodiment, 1 mg of the carbon nanotube sample prepared in the fifth embodiment, 1 mg of the carbon nanotube sample prepared in the sixth embodiment, 1 mg of the carbon nanotube sample prepared in the seventh embodiment, 1 mg of the carbon nanotube sample prepared in the eighth embodiment, 1 mg of the carbon nanotube sample prepared in the ninth embodiment, 1 mg of the carbon nanotube sample prepared in the tenth embodiment, 1 mg of the carbon nanotube sample prepared in the eleventh embodiment, 1 mg of the carbon nanotube sample prepared in the twelfth embodiment, and 1 mg of the carbon nanotube sample prepared in the comparative example were respectively placed in a 2% (w / w) sodium deoxycholate aqueous solution, ultrasonically treated for 90 minutes using an ultrasonic homogenizer, and centrifuged for 90 minutes using a micro-crystal centrifuge. The supernatant obtained by centrifugation was measured using a UV-Vis-NIR spectrophotometer with an optical path of 10 mm.

[0105] The absorption spectra of the carbon nanotubes prepared in the first embodiment and the comparative embodiment are as follows: Figure 19 As shown, the absorption spectrum intensity of the carbon nanotube sample prepared in the first embodiment is significantly higher than that of the corresponding comparative embodiment, indicating that the introduction of silica has a promoting effect on the growth of carbon nanotubes.

[0106] The absorption spectra of the carbon nanotubes prepared in the second embodiment and the comparative embodiment are as follows: Figure 20As shown, the absorption spectral intensity of the carbon nanotube sample prepared in the second embodiment is significantly higher than that of the corresponding comparative embodiment, indicating that the introduction of silicon element has a promoting effect on the growth of carbon nanotubes.

[0107] The absorption spectra of the carbon nanotubes prepared in the third embodiment and the comparative embodiment are as follows: Figure 21 As shown, the absorption spectrum intensity of the carbon nanotube sample prepared in the third embodiment is significantly higher than that of the corresponding comparative embodiment, indicating that the introduction of potassium phosphate has a promoting effect on the growth of carbon nanotubes.

[0108] The absorption spectra of the carbon nanotubes prepared in the fourth embodiment and the comparative embodiment are as follows: Figure 22 As shown, the absorption spectrum intensity of the carbon nanotube sample prepared in the fourth embodiment is significantly higher than that of the corresponding comparative embodiment, indicating that the introduction of titanium hydroxide has a promoting effect on the growth of carbon nanotubes.

[0109] The absorption spectra of the carbon nanotubes prepared in the fifth embodiment and the comparative embodiment are as follows: Figure 23 As shown, the absorption spectrum intensity of the carbon nanotube sample prepared in the fifth embodiment is significantly higher than that of the corresponding comparative embodiment, indicating that the introduction of manganese monoxide has a promoting effect on the growth of carbon nanotubes.

[0110] The absorption spectra of the carbon nanotubes prepared in the sixth embodiment and the comparative embodiment are as follows: Figure 24 As shown, the absorption spectrum intensity of the carbon nanotube sample prepared in the sixth embodiment is significantly higher than that of the comparative embodiment, indicating that the introduction of copper chloride has a promoting effect on the growth of carbon nanotubes.

[0111] The absorption spectra of the carbon nanotubes prepared in the seventh embodiment and the comparative embodiment are as follows: Figure 25 As shown, the absorption spectrum intensity of the carbon nanotube sample prepared in the seventh embodiment is significantly higher than that of the comparative embodiment, indicating that the introduction of zinc chloride has a promoting effect on the growth of carbon nanotubes.

[0112] The absorption spectra of the carbon nanotubes prepared in the eighth embodiment and the comparative embodiment are as follows: Figure 26 As shown, the absorption spectrum intensity of the carbon nanotube sample prepared in the eighth embodiment is significantly higher than that of the corresponding comparative embodiment, indicating that the introduction of sodium molybdate has a promoting effect on the growth of carbon nanotubes.

[0113] The absorption spectra of the carbon nanotubes prepared in the ninth embodiment and the comparative embodiment are as follows: Figure 27As shown, the absorption spectrum intensity of the carbon nanotube sample prepared in the ninth embodiment is significantly higher than that of the corresponding comparative embodiment, indicating that the introduction of lanthanum sulfate has a promoting effect on the growth of carbon nanotubes.

[0114] The absorption spectra of the carbon nanotubes prepared in the tenth embodiment and the comparative embodiment are as follows: Figure 28 As shown, the absorption spectrum intensity of the carbon nanotube sample prepared in the tenth embodiment is significantly higher than that of the comparative embodiment, indicating that the introduction of tantalum oxide promotes the growth of carbon nanotubes.

[0115] The absorption spectra of the carbon nanotubes prepared in the eleventh embodiment and the comparative embodiment are as follows: Figure 29 As shown, the absorption spectrum intensity of the carbon nanotube sample prepared in the eleventh embodiment is significantly higher than that of the corresponding comparative embodiment, indicating that the introduction of tungsten trioxide has a promoting effect on the growth of carbon nanotubes.

[0116] The absorption spectra of the carbon nanotubes prepared in the twelfth embodiment and the comparative embodiment are as follows: Figure 30 As shown, the absorption spectral intensity of the carbon nanotube sample prepared in the twelfth embodiment is significantly higher than that of the corresponding comparative embodiment, indicating that the introduction of lead monoxide promotes the growth of carbon nanotubes.

[0117] Specifically, the carbon nanotubes prepared in the sixth embodiment, the eighth embodiment, and the comparative embodiment were subjected to thermogravimetric analysis in air at a heating rate of 10 °C / min using a synchronous thermal analyzer.

[0118] The thermogravimetric curve and its first derivative of the carbon nanotubes prepared in the sixth embodiment are shown below. Figure 31 As shown, the carbon nanotube content in the sample prepared in the sixth embodiment is very high, at 37.31%, indicating that the introduction of copper chloride has a promoting effect on the growth of carbon nanotubes.

[0119] The thermogravimetric curve and its first derivative of the carbon nanotubes prepared in the eighth embodiment are shown below. Figure 32 As shown, the sample prepared in the eighth embodiment has a high carbon nanotube content of 27.90%, indicating that the introduction of sodium molybdate has a promoting effect on the growth of carbon nanotubes.

[0120] Among them, the thermogravimetric curves and their first derivatives of the carbon nanotubes prepared in the comparative example are as follows: Figure 33 As shown, the carbon nanotube content in the sample prepared in the comparative example is relatively low, at 10.19%, indicating that the introduction of component A, which has no catalytic activity, promotes the growth of carbon nanotubes.

[0121] It should be noted that the above detailed descriptions are exemplary and intended to provide further explanation of this application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains.

[0122] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the exemplary embodiments according to this application. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.

[0123] It should be noted that the terms "first," "second," etc., used in the specification, claims, and accompanying drawings of this application are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such terms can be used interchangeably where appropriate so that the embodiments of this application described herein can be implemented in sequences other than those illustrated or described herein.

[0124] Furthermore, the terms “comprising” and “having”, and any variations thereof, are intended to cover non-exclusive inclusion. For example, a process, method, system, product, or apparatus that includes a series of steps or units is not necessarily limited to those steps or units that are explicitly listed, but may include other steps or units that are not explicitly listed or that are inherent to such process, method, product, or apparatus.

[0125] For ease of description, spatial relative terms such as "above," "on top of," "on the upper surface of," "above," etc., are used herein to describe the spatial positional relationship of a device or feature as shown in the figures to other devices or features. It should be understood that spatial relative terms are intended to encompass different orientations in use or operation beyond the orientation of the device as described in the figures. For example, if the device in the figures were inverted, a device described as "above" or "on top of" other devices or structures would subsequently be positioned as "below" or "under" other devices or structures. Thus, the exemplary term "above" can include both "above" and "below." The device may also be positioned in other different ways, such as rotated 90 degrees or in other orientations, and the spatial relative descriptions used herein will be interpreted accordingly.

[0126] In the detailed description above, reference has been made to the accompanying drawings, which form part of this document. In the drawings, similar symbols typically identify similar parts unless the context otherwise indicates otherwise. The illustrated embodiments described in the detailed specification, drawings, and claims are not intended to be limiting. Other embodiments may be used and other changes may be made without departing from the spirit or scope of the subject matter presented herein.

[0127] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing single-walled carbon nanotubes by arc discharge, characterized in that, The method includes: An anode comprising a metal catalyst, a carbon raw material, and a non-catalytically active component A is prepared. The anode and a pure graphite rod cathode are placed in an electric arc furnace. The non-catalytically active component A comprises elemental silicon, elemental phosphorus, elemental arsenic, elemental selenium, elemental tellurium, elemental iodine, oxides of silicon, oxides of phosphorus, oxides of arsenic, oxides of selenium, oxides of tellurium, oxides of iodine, oxides of titanium, oxides of vanadium, oxides of manganese, oxides of copper, oxides of zinc, oxides of germanium, oxides of niobium, oxides of molybdenum, oxides of silver, oxides of tin, oxides of antimony, oxides of lanthanum, oxides of tantalum, oxides of tungsten, oxides of lead, oxides of bismuth, hydroxides of titanium, hydroxides of vanadium, hydroxides of manganese, hydroxides of copper, and hydroxides of zinc. One or more of the following: germanium hydroxide, niobium hydroxide, molybdenum hydroxide, silver hydroxide, tin hydroxide, antimony hydroxide, lanthanum hydroxide, tantalum hydroxide, tungsten hydroxide, lead hydroxide, bismuth hydroxide, salts containing silicon, salts containing phosphorus, salts containing arsenic, salts containing selenium, salts containing tellurium, salts containing iodine, salts containing vanadium, salts containing manganese, salts containing copper, salts containing zinc, salts containing germanium, salts containing niobium, salts containing molybdenum, salts containing silver, salts containing tin, salts containing antimony, salts containing lanthanum, salts containing tantalum, salts containing tungsten, salts containing lead, and salts containing bismuth; A set atmosphere is introduced into the electric arc furnace, the cathode and anode are brought into contact and a set current is passed through. After conduction, the distance between the cathode and anode is increased to maintain the electric arc discharge. Under the action of the electric arc, the anode is continuously consumed, and the generated gray-black carbon nanotube products are collected on the furnace wall.

2. The method for preparing single-walled carbon nanotubes by arc discharge according to claim 1, characterized in that, Component A, which is not catalytically active, is one or more of the following: silicon oxide, phosphorus oxide, titanium oxide, manganese oxide, copper oxide, zinc oxide, molybdenum oxide, tungsten oxide, titanium hydroxide, manganese hydroxide, copper hydroxide, zinc hydroxide, molybdenum hydroxide, tungsten hydroxide, salts containing silicon, salts containing phosphorus, salts containing titanium, salts containing manganese, salts containing copper, salts containing zinc, salts containing molybdenum, and salts containing tungsten.

3. The method for preparing single-walled carbon nanotubes by arc discharge according to claim 1, characterized in that, Component A, which does not have catalytic activity, is made of elemental silicon, silicon dioxide, potassium phosphate, titanium hydroxide, manganese monoxide, copper chloride, zinc chloride, sodium molybdate, lanthanum sulfate, tantalum oxide, tungsten trioxide, or lead monoxide.

4. The method for preparing single-walled carbon nanotubes by arc discharge according to claim 1, characterized in that, The metal catalyst is one or more of the following: scandium, chromium, iron, cobalt, nickel, yttrium, zirconium, ruthenium, rhodium, palladium, cerium, rhenium, osmium, iridium, scandium oxide, chromium oxide, iron oxide, cobalt oxide, nickel oxide, yttrium oxide, zirconium oxide, ruthenium oxide, rhodium oxide, palladium oxide, cerium oxide, rhenium oxide, osmium oxide, iridium oxide, scandium sulfide, chromium sulfide, iron sulfide, cobalt sulfide, nickel sulfide, yttrium sulfide, zirconium sulfide, ruthenium sulfide, rhodium sulfide, palladium sulfide, cerium sulfide, rhenium sulfide, osmium sulfide, and iridium sulfide.

5. The method for preparing single-walled carbon nanotubes by arc discharge according to claim 4, characterized in that, The metal catalyst is selected from two or three of the following: elemental iron, elemental cobalt, elemental nickel, elemental yttrium, iron oxide, cobalt oxide, nickel oxide, yttrium oxide, iron sulfide, cobalt sulfide, nickel sulfide, and yttrium sulfide.

6. The method for preparing single-walled carbon nanotubes by arc discharge according to claim 1, characterized in that, The amount of component A, which has no catalytic activity, is 0-100 times that of the metal catalyst, and the amount of component A, which has no catalytic activity, is 0-5 times that of the carbon raw material.

7. The method for preparing single-walled carbon nanotubes by arc discharge according to claim 1, characterized in that, The atmosphere introduced into the electric arc furnace is one or two of hydrogen, helium, nitrogen, and argon.

8. The method for preparing single-walled carbon nanotubes by arc discharge according to claim 1, characterized in that, Before the cathode and anode come into contact, the total pressure in the electric arc furnace is 30 kPa-100 kPa.

9. The method for preparing single-walled carbon nanotubes by arc discharge according to claim 1, characterized in that, During the arc discharge process, the distance between the cathode and the anode is 1mm-20mm.

10. The method for preparing single-walled carbon nanotubes by arc discharge according to claim 1, characterized in that, The current of the arc discharge is 40-80A, and the voltage of the arc discharge is 15-50V.

Citation Information

Patent Citations

  • Method for batch type production of single-wall nano carbon tube suing temperature-controlled electric arc furnace

    CN1579931A

  • Arc synthesis of single-wall carbon nanometer tubes

    CN1712349A